Social Sciences and Rural Studies in Argentina during the 20th century (Alternautas, 2022)
This work intends to provide a broad overview of social science contributions in the study of Argentinian agrarian processes and rural contexts. It is intended as a way of organising the literature without too much of a focus on its theoretical or methodological underpinnings. Regardless, the mere fact of selecting some works and not others involves decisions that are not exempt from some kind of academic evaluation. This is evident particularly in the last period in which, surprisingly, I found an abundant and heterogenous production.